Continuous Subcutaneous Delivery of Proline-Rich Antimicrobial Peptide Api137 Provides Superior Efficacy to Intravenous Administration in a Mouse Infection Model - Knappe, Daniel; Schmidt, Rico; Adermann, Knut; Hoffmann, Ralf (Frontiers in Microbiology, 2019)
Apidaecins are cationic, proline-rich antimicrobial peptides originally isolated from honeybees and exhibit high Gram-negative activity by inhibiting bacterial protein translation. Pharmacokinetics of apidaecin derivative Api137 was studied using single and multiple intravenous or subcutaneous injection as well as continuous subcutaneous infusion and correlated to its efficacy in a lethal murine Escherichia coli infection model. Survival rates of infected CD 1 mice were monitored and Api137 and its metabolites were quantified in plasma of uninfected CD-1 mice and Sprague Dawley rats using reversed-phase chromatography coupled online to mass spectrometry. The highest Api137 plasma levels of 23 mg/L were obtained after a single intravenous injection of 20 mg/kg body weight, which declined fast over the next 120 minutes (half-life <30 min). In contrast, continuous subcutaneous infusion of a similar dose over an hour (19.4 mg/kg/hr) lead to stable plasma levels of ~6 mg/L, which was above the minimal inhibitory concentration against E. coli ATCC 25922 (4 mg/L). The increased exposure by continuous subcutaneous administration of Api137 at 19.4 mg/kg/hr over 48 h improved efficacy in the murine intraperitoneal sepsis model with survival of 67 % over 5 days compared to 33% after intravenous and subcutaneous administration in different dosing schemes. To the best of our knowledge, continuous subcutaneous infusion using osmotic pumps was successfully utilized for delivery of an antimicrobial peptide for the first time. Additionally, the potential of apidaecin analogs as novel antibiotics is demonstrated even in a scenario where the infection site is clearly separated from the route of apidaecin administration.